When the Cycle Becomes the Trend : The Emerging Market Experience with Fiscal Policy during the Last Commodity Super Cycle - Amra, Rashaad; Hanusch, Marek; Jooste, Charl (World Bank, Washington, DC, 2019)
Fiscal buffers have shrunk across the world. This paper argues that limited fiscal room in emerging market economies today is partly due to the commodity super cycle of 2000-15. The super cycle created the mirage that economic performance had structurally improved, mistaking a long, commodity-fueled uptick in the business cycle for higher trend growth. This thinking supported fiscal expansions. When the commodity boom ended, it became apparent that countries had saved less than they should have, and that fiscal policy had, perhaps inadvertently, been pro-cyclical. It left countries with depleted fiscal buffers and large budgets when the cycle came to an end, limiting room for fiscal stimulus when needed. The paper illustrates the argument with reference to the South African experience.